REVITALIZING PUBLIC SERVICE: ASSESSING THE SUCCESS OF ONLINE SINGLE SUBMISSION (OSS) POLICY AT INVESTMENT AND INTEGRATED SERVICE OFFICE - Rahman, Fidyawati Abdul; Isa, Rusli; Tantu, Romy (Universitas Negeri Gorontalo, 2024)
This study aims to determine (1) the implementation of the Online Single Submission (OSS) policy at the Investment and One-Stop Integrated Services Office (DPM-PTSP) of Gorontalo Regency (2) the factors that determine the implementation of the Online Single Submission (OSS) policy at the Investment and One-Stop Integrated Services Office (DPM-PTSP) of Gorontalo Regency. The approach used is qualitative with a type of descriptive research. Data collection using interviews, observation and documentation. Data analysis using the Miles and Huberman model. The results of this study show that (1) The implementation of OSS policy in DPM-PTSP Gorontalo Regency has been implemented quite well and provides benefits in facilitating the licensing service process. The use of the OSS system has helped the OSS user community in carrying out licensing tasks more easily and increased the effectiveness of licensing services in DPM-PTSP. In addition, OSS also provides benefits in increasing productivity and work performance of users in DPM-PTSP. Overall, OSS in DPM-PTSP Gorontalo Regency has proven useful in supporting licensing service tasks but still more must be developed and innovated to be simpler but with better benefits. (2) Factors that determine the implementation of the Online Single Submission (OSS) policy at the Investment and One-Stop Integrated Services Office (DPM-PTSP) of Gorontalo Regency are categorized as quite good because of supporting factors (policy standards and objectives, characteristics of implementing organizations and attitudes of implementers) and some that hinder or have not been effective (resources, communication between organizations and external socioeconomic and political factors),Â where this shows that various aspects that determine the implementation of OSS policies have been well managed in an effort to improve the efficiency and effectiveness of licensing services. Efforts to implement OSS policies in DPM-PTSP Gorontalo Regency have produced positive impacts and have improved the process of integrated licensing services.